Comparison of Femtosecond Laser-Assisted Cataract Surgery and Conventional Phacoemulsification in Shallow Anterior Chambers and Glaucoma - Zhou Zhou; Li Li; Siming Zeng; Wenjing He; Min Li (Journal of Ophthalmology)
Purpose. To compare femtosecond laser-assisted cataract surgery (FLACS) versus conventional phacoemulsification in shallow anterior chamber cataract patients with glaucoma or zonulysis. Methods. This was a single-center retrospective review of cataract surgeries in shallow anterior chamber and glaucoma patients between January 2016 and December 2018 in which a LenSx femtosecond laser was used. The outcome measures included pre- and postoperative uncorrected and corrected distance visual acuity (UDVA and CDVA), intraocular pressure (IOP), endothelial cell density (ECD), endothelial cell loss (ECL), and object scatter index (OSI). Results. One hundred and six eyes of 106 patients with a mean anterior chamber depth of 1.54 ± 0.51 mm were included in this study. Among them, 26 (23.2%) had zonulysis and 18 eyes had capsular tension ring implantation in general. The percentage of capsular tension ring implantation was statistically significantly lower in the FLACS group (P = 0.027). The UDVA, CDVA, ECD, and IOP were not statistically significant between the two groups at all time points. The postoperative ECL and OSI of the FLACS group was better than those of the conventional group (P < 0.01). Conclusions. FLACS can reduce ECL and improve visual quality compared to the conventional phacoemulsification in shallow anterior chamber patients. Also, it has the trend of reducing the use of capsular tension rings in subluxated cataracts. It is an ideal choice for patients with complicated cataract such as with shallow anterior chambers, glaucoma, and zonulysis.